SELF-EFFICACY AND SOCIAL SUPPORT OF PARENTS AS PREDICTORS OF CAREER DECISION MAKING IN SENIOR HIGH SCHOOL - Ruseno Arjanggi (LPPM University 17 Agustus 1945 Samarinda, 2021)
This research aimed to test the role of self-efficacy and parent social support to career decision making in senior high school. This research used a quantitative method. The samples analysis were 416 students of senior high school in Semarang. Sampling methods using cluster random sampling Instruments used in this research consist of three scales. Career decision scale (CDS) consisted 19 items statement with corrected item-total correlation coefficient range 0,325-0,597; internal consistency Alpha 0,887. Self efficacy scale consisted 28 items statement, with corrected item-total correlation coefficient range 0,335-0,428; internal consistency Alpha 0,851, and social support scale consisted of 40 items, with corrected item-total correlation coefficient range 0,335-0,428 and internal consistency Alpha 0,941. Data analysis using multiple regression analysis. The result showed a significant relationship between self-efficacy and social support of parents with career decision making in senior high school students with R = 0,664 and F = 163,172 with significant = 0,000 (p<0,01). The correlation between self-efficacy and career decision making obtained rx1y0,555, p = 0,000 (p<0,01), which means there is a significant correlation between self-efficacy with career decision making in senior high school students. Result of correlation between social support of parents with career decision making obtained rx2y = 0,572 p = 0,000 (p<0,01). The results showed a significant correlation between social support of parents and career decision making. Effective contribution of self-efficacy and social support of parents in this research was 44,1%. Keywords: career decision, self-efficacy and social support